The simulation of project management-quality of software developed / Heng Ai Shi - Heng , Ai Shi (2004)
The Simulation of Project Management is a stand-alone application that aims to prepare future project leaders by providing simulated project management experience and be used by students who are taking Project Management course to test their knowledge on this course and therefore increase their interest and skill in handling project in future. Basically, the Simulation of Project Management will inform the results to the player after the simulation end from the following perspectives: project schedule, project cost, resource management and quality of the software developed by the project team members. The Simulation of Project Management is divided into 8 main modules which are: Overall Project Schedule, Team Organization, Manpower/Budget Schedule, Team Member Schedule, Project Leader Schedule, Module Design/Coding'Module Test Progress Table, Integration Test Progress Table and Simulation Result Screen. This system was developed on Microsoft Windows XP Professional platform using Microsoft Visual Basic.NET with Macromedia Flash MX supported. Besides, the Database Management System (DBMS) for the Simulation of Project Management is Microsoft Access 2000, which is the most popular database nowadays. Literature reviews on all topics involved have been conducted to determine the feasibility of the system. All these activities are aimed at achieving the best outcome, which is to create a comprehensive Simulation of Project Management to fulfill the needs and satisfaction of the player.